Best Answer

To solve for h, first isolate 4h:

T=4h+4z

T-4z=4h

Now divide both sides by 4.

T/4-z=h

Q: T equals 4h plus 4z the solution is h equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

9z

7 + 4z = 437 + 4z -7 = 43 - 7 4z = 43 - 7 4z = 36 z = 9

its 10x +9y +1z

-6z 2 = 3z+ 4z+28 -6z+2 +3z = 3z+ 4z +28 +4z -6z+4z+2 = 3z+ 28 -10z+2 -3z= 28 - 2 -10z + -3z = 26 -13z/13 = 26/-13 z = -2

4z-11=45 4z=56 z=14

Related questions

-8z + 12 = 12 - 4z-8z +4z + 12 = 12 - 4z +4z-4z + 12 -12 = 12 -12-4z / -4 = 0 / -4z = 0:)

9z

7 + 4z = 437 + 4z -7 = 43 - 7 4z = 43 - 7 4z = 36 z = 9

6z-4z-z = 6-7-4 z = -5

its 10x +9y +1z

3y + 4z + 12y = 3y -3y -3y ------------------------- 4z + 12y = 0 divide everything by 4 z + 3y = 0 -3y -3y z = -3y

-6z 2 = 3z+ 4z+28 -6z+2 +3z = 3z+ 4z +28 +4z -6z+4z+2 = 3z+ 28 -10z+2 -3z= 28 - 2 -10z + -3z = 26 -13z/13 = 26/-13 z = -2

5x-2y+3z-2x-y-4z=3x-3y-z

That depends entirely on what the value of z is.

(z=-3) and (z=7)

7x + y + z = 6 7x + y + 4z = 9 y + x = 6 Take the first two statements and subtract them. 7x + y + z = 6 7x + y + 4z = 9 _____________ 0 + 0 - 3z = -3 Therefore: z = 1 Then you are left with: 7x + y + 1 = 6 7x + y + 4 = 9 which is impossible, so this is an impossible equation.

4z-11=45 4z=56 z=14